Correlation between initial SiO2/Al2O3, Na2O/Al2O3, Na2O/SiO2 and H2O/Na2O ratios on phase and microstructure of reaction products of metakaolin-rice husk ash geopolymer - K. Juengsuwattananon (2019)
© 2019 Elsevier Ltd Phase evolution and microstructure development of metakaolin-rice husk ash geopolymer have been investigated. The initial molar ratios of SiO2/Al2O3 were designed in the range of 2.0–7.0 with Na2O/Al2O3 ratios of 0.6–1.6, Na2O/SiO2 of 0.20–0.72 and H2O/Na2O of 10.0–20.0. The specimens were cured at 30 °C for 1–90 days prior to characterization of phase and microstructure as well as mechanical properties. The designed molar ratios were found to correlate with phase and microstructure of reaction products related to their compressive properties. Various zeolite types (sodalite, zeolite A, zeolite Y, zeolite X and faujasite) were prominently observed in samples containing low initial molar ratios of SiO2/Al2O3 (2.0–2.5) with Na2O/Al2O3 ≥ 1.0 and H2O/Na2O in the range of 10.0–20.0. These low SiO2/Al2O3 ratios provided low strength geopolymer. Formation of geopolymeric structures was established in samples containing higher initial molar ratio of SiO2/Al2O3 (3.0–4.0) with Na2O/Al2O3 ratio of 1.0 and H2O/Na2O ratios in the range of 10.0–15.0. The highest strength was achieved when initial molar ratios of SiO2/Al2O3, Na2O/Al2O3 and H2O/Na2O were 4.0, 1.0 and 10.0, respectively. When the initial molar ratios of SiO2/Al2O3 increased to 6.0–7.0 with Na2O/Al2O3 ratios of 1.0–1.6 and H2O/Na2O ratios of 10.0–15.0, sodium bicarbonate compounds and unreacted raw materials were observed within the geopolymeric structures. Correlation of phase structures of reaction products with different starting chemical compositions were evaluated and revealed in a ternary composition diagram.